2021
DOI: 10.21203/rs.3.rs-1076903/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and Effectiveness of Mepolizumab Therapy in Remission Induction Therapy for Eosinophilic Granulomatosis with Polyangiitis: A Retrospective Study

Abstract: Objectives: To investigate the safety and effectiveness of mepolizumab (MPZ), an anti-interleukin-5 antibody, as remission induction therapy for severe eosinophilic granulomatosis with polyangiitis (EGPA).Methods: The clinical courses of patients with severe EGPA over 6 months were retrospectively investigated and compared between patients treated with high-dose corticosteroid (CS) plus MPZ therapy (MPZ group, n=7) and those treated with high-dose CS plus intravenous cyclophosphamide (IVCY) pulse therapy (IVCY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…We had a high number of patients from a single center for a study showing the efficacy of lowdose mepolizumab in EGPA, which has a low prevalence of 23 cases/million people [24]. Moreover, when looked at the literature, the number of patients in our study was higher than those in other single-center studies [7,8,16,21,23]. In addition, mepolizumab increased asthma-related quality of life in EGPA patients even at low doses, and it was important that our study was the first real-life study to demonstrate data in this regard.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We had a high number of patients from a single center for a study showing the efficacy of lowdose mepolizumab in EGPA, which has a low prevalence of 23 cases/million people [24]. Moreover, when looked at the literature, the number of patients in our study was higher than those in other single-center studies [7,8,16,21,23]. In addition, mepolizumab increased asthma-related quality of life in EGPA patients even at low doses, and it was important that our study was the first real-life study to demonstrate data in this regard.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, mepolizumab increased asthma-related quality of life in EGPA patients even at low doses, and it was important that our study was the first real-life study to demonstrate data in this regard. Short term follow-up period may be considered a limitation in such studies as indicated in Ueno et al [16,23]. Although all of our patients did not reach to the 12th month, we did overcome this limitation by using mixedeffect regression model, a full-likelihood method that takes all of the available data into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation